2009
DOI: 10.1590/s0104-07072009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Organização do trabalho de enfermagem na Atenção Básica: uma questão para a saúde do trabalhador

Abstract: RESUMO:Estudo sobre o impacto da organização do trabalho de enfermeiros, técnicos e auxiliares de enfermagem na Atenção Básica e a sua relação com a saúde destes trabalhadores. Estudo transversal, descritivo e inferencial, com análise bivariada usando o quiquadrado de Pearson. Amostra intencional de 171 profissionais, aplicando-se um questionário fechado com perguntas individuais e um formulário de observação. Escores de insatisfação altos foram obtidos nos itens relação com a chefia (83,6%), com colegas (76,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
35

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 12 publications
1
23
0
35
Order By: Relevance
“…The research institution showed a distinct reality, however, in which items like work conditions are precarious, the physical environment is uncomfortable, the work instruments are insufficient to do the work, the workplace is inadequate to perform the tasks, the equipment needed to perform the tasks is precarious, the physical space to perform the work is inadequate, the work conditions offer risks to people and the consumption material is insufficient were assessed satisfactorily. The difficulties and precariousness of work conditions in the Brazilian public and private health context is known, in which negligence and precarious structural and material conditions imply risks for clients and workers' health (17) .…”
Section: Task Is Defined As [] Operationalization Of Prescribed Womentioning
confidence: 99%
“…The research institution showed a distinct reality, however, in which items like work conditions are precarious, the physical environment is uncomfortable, the work instruments are insufficient to do the work, the workplace is inadequate to perform the tasks, the equipment needed to perform the tasks is precarious, the physical space to perform the work is inadequate, the work conditions offer risks to people and the consumption material is insufficient were assessed satisfactorily. The difficulties and precariousness of work conditions in the Brazilian public and private health context is known, in which negligence and precarious structural and material conditions imply risks for clients and workers' health (17) .…”
Section: Task Is Defined As [] Operationalization Of Prescribed Womentioning
confidence: 99%
“…No contexto de trabalho aparece o fator "as condições de trabalho oferecem riscos à segurança das pessoas" uma vez que a escassez de equipamentos necessários para os atendimentos, faz com que o profissional fique exposto a diversos riscos tanto para si mesmo quanto para o paciente, gerando a sensação de tarefa incompleta 15 . O profissional da equipe de enfermagem enfrenta pressões para trabalhar em certas situações com falta de equipamentos e materiais, o que implica em não seguir corretamente suas metas de segurança no cuidado 15 , ficam expostos constantemente há vários riscos que podem acarretar problemas de saúde ou acidentes de trabalho 16 .…”
unclassified
“…This demonstrates the breakdown of the care model centered on the doctor, who has an eminently caring and curative character (10) .…”
Section: Discussionmentioning
confidence: 99%
“…A study on the impact of the organization of the work of nurses, technicians and nursing assistants concluded that it is necessary to look specifically at the organization of work in PHC because this environment, unlike the hospital, calls for more diversity in the activities of nursing staff and nurses in particular (10) .…”
Section: Introductionmentioning
confidence: 99%